Answer:
cant see it
Step-by-step explanation:
Okay here you go hope this helps you..
its 3 pictures by the way
Answer:
9. 2a+5 ; 11. 2x+11y+4 ; 13. -a+3b-1 ; 15. (10c^2)-2c+5 ; 17. (5(a^2)(b^2))-(a(b^2))
Step-by-step explanation:
You should group each term with the same variables and then simplify
9. 9a + 8 - 2a - 3 - 5a
=(9a-2a-5a)+(8-3)
= 2a + 5
11. 7x + 2y + 5 - 5x + 9y - 1
= (7x-5x)+(2y+9y)+(5-1)
=2x+11y+4
13. -6+3a-b-4a+4b+5
=(3a-4a)+(-b+4b)+(-6+5)
=-a+3b-1
15. 8c^2 -c+3+2c^2 -c +2
=(8c^2 + 2c^2)+(-c-c)+(3+2)
=(10c^2)-2c+5
17. 6a^2b^2 + 3ab^2 -a^2b^2 -4ab^2
=(6a^2b^2 -a^2b^2)+(3ab^2 -4ab^2)
=(5(a^2)(b^2))-(a(b^2))
Answer:
greatest to lowest:
2.841
2.841
2.841
and finally,
2.830
lowest to greatest
2.830
2.841
2.841
2.841
Answer:
x≥2.56
Step-by-step explanation:
first we can write the inequality
2+9x≥25
we can now solve this with algebra
9x≥23
x≥2.56
2/5
3/5
3/8
Answer:
3/5
Step-by-step explanation:
PO/OS=6/10=(3*2)/(5*2)=3/5
Answer:
The answer is 3/5